The presence of cortical neurons in striatal-cortical co-cultures alters the effects of dopamine and BDNF on medium spiny neuron dendritic development - Penrod, Rachel D.; Campagna, Justin; Panneck, Travis; Preese, Laura; Lanier, Lorene M. (Frontiers in Cellular Neuroscience, 2015)
Medium spiny neurons (MSNs) are the major striatal neuron and receive synaptic input from both glutamatergic and dopaminergic afferents. These synapses are made on MSN dendritic spines, which undergo density and morphology changes in association with numerous disease and experience-dependent states. Despite wide interest in the structure and function of mature MSNs, relatively little is known about MSN development. Furthermore, most in vitro studies of MSN development have been done in simple striatal cultures that lack any type of non-autologous synaptic input, leaving open the question of how MSN development is affected by a complex environment that includes other types of neurons, glia, and accompanying secreted and cell-associated cues. Here we characterize the development of MSNs in striatal-cortical co-culture, including quantitative morphological analysis of dendritic arborization and spine development, describing progressive changes in density and morphology of developing spines. Overall, MSN growth is much more robust in the striatal-cortical co-culture compared to striatal mono-culture. Inclusion of dopamine in the co-culture further enhances MSN dendritic arborization and spine density, but the effects of dopamine on dendritic branching are only significant at later times in development. In contrast, exogenous Brain Derived Neurotrophic Factor (BDNF) has only a minimal effect on MSN development in the co-culture, but significantly enhances MSN dendritic arborization in striatal mono-culture. Importantly, inhibition of NMDA receptors in the co-culture significantly enhances the effect of exogenous BDNF, suggesting that the efficacy of BDNF depends on the cellular environment. Combined, these studies identify specific periods of MSN development that may be particularly sensitive to perturbation by external factors and demonstrate the importance of studying MSN development in a complex signaling environment.